2021
DOI: 10.1016/j.stemcr.2021.10.011
|View full text |Cite
|
Sign up to set email alerts
|

IL-18R-mediated HSC quiescence and MLKL-dependent cell death limit hematopoiesis during infection-induced shock

Abstract: Summary Severe infection can dramatically alter blood production, but the mechanisms driving hematopoietic stem and progenitor cell (HSC/HSPC) loss have not been clearly defined. Using Ixodes ovatus Ehrlichia (IOE), a tick-borne pathogen that causes severe shock-like illness and bone marrow (BM) aplasia, type I and II interferons (IFNs) promoted loss of HSPCs via increased cell death and enforced quiescence. IFN-αβ were required for increased interleukin 18 (IL-18) expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Flow cytometric staining was performed as previously described ( Howard et al., 2021 ). Spleen and whole BM, flushed from femurs and tibias, were processed and then filtered through a 70 μm filter.…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometric staining was performed as previously described ( Howard et al., 2021 ). Spleen and whole BM, flushed from femurs and tibias, were processed and then filtered through a 70 μm filter.…”
Section: Methodsmentioning
confidence: 99%
“…IL-18R expression has been detected in bone-marrow progenitor cells [ 151 , 152 ]. Furthermore, IL-18 produced during inflammation can reduce hematopoietic stem cell differentiation [ 152 , 153 ].…”
Section: Ilc Plasticity In Response To Lung Infectionsmentioning
confidence: 99%
“…IL-18R expression has been detected in bone-marrow progenitor cells [ 151 , 152 ]. Furthermore, IL-18 produced during inflammation can reduce hematopoietic stem cell differentiation [ 152 , 153 ]. Additionally, a recent work suggests that IL-18R signaling is dispensable for ILC development but inhibits differentiation of ILCPs [ 151 ].…”
Section: Ilc Plasticity In Response To Lung Infectionsmentioning
confidence: 99%
“…Additional work has also shown that IFNα/β is required for the increase of IL-18 expression during infection processes leading to loss of short-term HSCs. Absence of IL-18 was shown to prevent BM aplasia and increase HSCs/HSPCs ( 125 ).…”
Section: Necroptosis and Pyroptosis Cause Bmf Under Inflammatory Cond...mentioning
confidence: 99%